2014
DOI: 10.2337/db13-1087
|View full text |Cite
|
Sign up to set email alerts
|

The Human GLP-1 Analogs Liraglutide and Semaglutide: Absence of Histopathological Effects on the Pancreas in Nonhuman Primates

Abstract: Increased pancreas mass and glucagon-positive adenomas have been suggested to be a risk associated with sitagliptin or exenatide therapy in humans. Novo Nordisk has conducted extensive toxicology studies, including data on pancreas weight and histology, in Cynomolgus monkeys dosed with two different human glucagon-like peptide-1 (GLP-1) receptor agonists. In a 52-week study with liraglutide, a dose-related increase in absolute pancreas weight was observed in female monkeys only. Such dose-related increase was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 48 publications
6
54
0
1
Order By: Relevance
“…Other long-term animal studies did not find a harmful effect of incretin-mimetic drugs on pancreatic tissue [164,165]. Furthermore, analyses from adverse reporting systems are useful, but are difficult to control for confounding factors that increase the risk of pancreatitis and cancer, such as obesity, alcohol consumption, smoking, and the use of other drugs.…”
Section: Cancermentioning
confidence: 99%
“…Other long-term animal studies did not find a harmful effect of incretin-mimetic drugs on pancreatic tissue [164,165]. Furthermore, analyses from adverse reporting systems are useful, but are difficult to control for confounding factors that increase the risk of pancreatitis and cancer, such as obesity, alcohol consumption, smoking, and the use of other drugs.…”
Section: Cancermentioning
confidence: 99%
“…Despite lack of evidence for GLP-1R expression in acinar cells of the rodent pancreas, several preclinical studies have demonstrated that GLP-1R agonists increase the mass of the pancreas, predominantly in mice (7,8) and in a subset of male nonhuman primates (9). Nevertheless, the increase in pancreatic weight following treatment with GLP-1R agonists has not been associated with histological abnormalities in the pancreas (3,9,10), and mechanistic explanations for changes in pancreatic mass have not been forthcoming.…”
mentioning
confidence: 99%
“…Nevertheless, the increase in pancreatic weight following treatment with GLP-1R agonists has not been associated with histological abnormalities in the pancreas (3,9,10), and mechanistic explanations for changes in pancreatic mass have not been forthcoming. We show here that exendin-4 (Ex-4) and liraglutide increase pancreatic weight via induction of protein synthesis, without changes in acinar cell proliferation or DNA content.…”
mentioning
confidence: 99%
“…In a human autopsy series, use of incretin-based therapies was associated with an increase in whole pancreas cell proliferation and presence of PanIN (Butler et al 2013a); however, a variety of methodological issues, such as differences between the studied groups with respect to age, gender, disease duration, and treatments, limit the ability to interpret this study (Drucker 2013;Kahn 2013;BonnerWeir, In't Veld, and Weir 2014). In contrast to studies suggesting a relationship between incretin therapy and proliferation of the exocrine pancreas, toxicology studies using liraglutide (Nyborg et al 2012;Gotfredsen et al 2014), exenatide (Tatarkiewicz et al 2010), lixisenatide (European Public Assessment Report, Lyxumia [EPAR] 2012), albiglutide (Mirabile, Kambara, and Maier 2013), semaglutide (Gotfredsen et al 2014), and sitagliptin (Engel et al 2010) did not detect proliferative lesions in the pancreas due to treatment nor were pancreatic tumors increased in rodent carcinogenicity studies. These studies included evaluation of pancreatic histology in mice, rats, dogs, and monkeys in toxicology studies that utilized relatively high doses of these agents.…”
Section: Discussionmentioning
confidence: 95%
“…One study of liraglutide administered to NHP at supraphysiological doses for 87 weeks did not report any pancreatic structural changes (Nyborg et al 2012). An additional report described a 52-week NHP study of liraglutide and 13-and 52-week NHP studies of semaglutide (a structurally different GLP-1 receptor agonist) and did not report any histopathologic alterations of the exocrine pancreas (Gotfredsen et al 2014).…”
Section: Introductionmentioning
confidence: 99%